The Contribution of Rice Farming to the Economic Welfare of the Community - Marlina, Marlina; Fatimah, Siti; Wargo; Poetro, Arief Eko (Zabags International Journal of Economy, 2025)
This study aims to examine the contribution of rice farming business to improving the economic welfare of the community in Simpang Datuk Village, Nipah Panjang District. The method used is a descriptive qualitative approach with data collection techniques through interviews and field observations. The results of the study show that rice farming makes a significant contribution to community income, access to education, and the fulfillment of basic needs. The strategies implemented by farmers include the use of agricultural technology, the selection of superior varieties, and the strengthening of local institutions. Nonetheless, challenges such as capital constraints, climate change, and selling prices remain obstacles that require appropriate policy interventions. The conclusion of this study confirms that rice farming has great potential in improving the economic welfare of rural communities in a sustainable manner.